Current animal models of extracorporeal cardiopulmonary resuscitation: A scoping review - Shinichi Ijuin; Keibun Liu; Denzil Gill; Sun Kyun Ro; Jana Vukovic; Satoshi Ishihara; Jan Belohlavek; Gianluigi Li Bassi; Jacky Y Suen; John F Fraser (Resuscitation Plus, 2023)
Aim: Animal models of Extracorporeal Cardiopulmonary Resuscitation (ECPR) focusing on neurological outcomes are required to further the development of this potentially life-saving technology. The aim of this review is to summarize current animal models of ECPR. Methods: A comprehensive database search of PubMed, EMBASE, and Web of Science was undertaken. Full-text publications describing animal models of ECPR between January 1, 2000, and June 30, 2022, were identified and included in the review. Data describing the conduct of the animal models of ECPR, measured variables, and outcomes were extracted according to pre-defined definitions. Results: The search strategy yielded 805 unique reports of which 37 studies were included in the final analysis. Most studies (95%) described using a pig model of ECPR with the remainder (5%) describing a rat model. The most common method for induction of cardiac arrest was a fatal ventricular arrhythmia through electrical stimulation (70%). 10 studies reported neurological assessment of animals using physical examination, serum biomarkers, or electrophysiological findings, however, only two studies described a multimodal assessment. No studies reported the use of brain imaging as part of the neurological assessment. Return of spontaneous circulation was the most reported primary outcome, and no studies described the neurological status of the animal as the primary outcome. Conclusion: Current animal models of ECPR do not describe clinically relevant neurological outcomes after cardiac arrest. Further work is needed to develop models that more accurately mimic clinical scenarios and can test innovations that can be translated to the application of ECPR in clinical medicine.